PEMANFAATAN MEDIA SOSIAL FACEBOOK PADA PENDAPATAN PERTANIAN JAGUNG DI DESA LAIBA KECAMATAN PARIGI KABUPATEN MUNA - Ade Graeni; Ima Astuty Wunawarsih; Megafirmawanti Lasinta (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
Social media has emerged as a significant conduit for the dissemination of information, with implications for the dissemination of information regarding corn production in Muna Regency. Corn in this region holds considerable potential as a strategic commodity, yet it is subject to variability in production, inadequate farming efficiency, and the challenges posed by unstable prices. Notwithstanding these challenges, cultivation and marketing opportunities for corn in Muna Regency remain promising. The objective of this study is to ascertain the utilization of Facebook social media during the corn cultivation process and to determine the income of corn farmers in Laiba Village, Parigi District, Muna Regency. The population under study comprised 102 corn farmers residing in Laiba Village. The sampling technique employed a simple random sampling method, yielding a sample of 30 respondents. The study's primary focus was on the following variables: farmer characteristics, utilization of Facebook social media, and income levels of corn farmers. The analysis was conducted using descriptive statistical analysis and income formulas. The findings indicated that the utilization of Facebook as a resource for information concerning cultivation and marketing endeavors was classified within the high category. Furthermore, the income level of corn farmers was found to be notably high. The capacity of farmers to access and utilize social media, particularly Facebook, has been identified as a strategic factor in the development and implementation of farming development strategies that are more conducive to optimal outcomes. These strategies have been shown to positively impact farmers' income.